Inherited Disorders of the Fibrinolytic Pathway: Pathogenic Phenotypes and Diagnostic Considerations of Extremely Rare Disorders - Al-Ghafry, Maha; Abou-Ismail, Mouhamed Yazan; Acharya, Suchitra S. (Seminars in Thrombosis and Hemostasis, 2024)
Fibrinolysis is initiated by the activation of plasminogen to plasmin via tissue-plasminogen activator (tPA) and urokinase-plasminogen activator (uPA); plasmin then converts fibrin to fibrin degradation products (FDPs). The antifibrinolytics counterbalancing this system include plasminogen activator inhibitor-1 (PAI-1), which inhibits tPA and uPA, α-2 antiplasmin (α2AP), which inhibits plasmin, and thrombin activatable fibrinolysis inhibitor, which inhibits the conversion of fibrin to FDP. Inherited disorders of the fibrinolytic pathway are rare and primarily have hemorrhagic phenotypes in humans: PAI-1 deficiency, α2AP deficiency, and Quebec platelet disorder. Patients with these disorders are usually treated for bleeds or receive prophylaxis to prevent bleeds in the surgical setting, with pharmacological antifibrinolytics such as aminocaproic acid and tranexamic acid. Disorders of the fibrinolytic pathway with fibrin deposition are extremely rare, mostly noted in patients with plasminogen deficiency, who have more recently benefited from advances in human plasma-derived plasminogen concentrates administered intravenously or locally. These disorders can be very difficult to diagnose using conventional or even specialized coagulation testing, as testing can be nonspecific or have low sensitivity. Testing of the corresponding protein's activity and antigen (where applicable) can be obtained in specialized centres, and routine laboratory measures are not diagnostic. Genetic testing of the pathogenic mutations is recommended in patients with a high suspicion of an inherited disorder of the fibrinolytic pathway.
Keywords: fibrinolysis; plasminogen activators; PAI-1; α-2 antiplasmin; plasminogen deficiency